Association between Sleep Deprivation in Caregivers and Risk of Injury among Toddlers: A Propensity Score Analysis. (23rd June 2020) - Chiu, I-Tsung; Huang, Ting-Yun; Ong, Jiann Ruey; Ou, Ju-Chi; Chen, Ping-Ling; Ma, Hon-Ping
Abstract : Introduction . Unintentional injury remains the leading cause of death in children worldwide. Adequate parental supervision is a crucial strategy for preventing injury. Many factors, such as a large family size, poor socioeconomic status, and the caregiver being a single mother, contribute to unintentional injury in children. In addition, sleep deprivation in caregivers might be associated with injury in children because sleep deprivation causes impaired daytime cognitive function, wake-state instability, and negative moods, thereby impairing caregiver supervision. Therefore, this study determines the association between injury in children and the sleep quality of their primary caregivers. Method . This is a retrospective case–control study on unintentional injury in children aged 0 to 4 years who visited the emergency department (case group) and an age- and sex-matched control group. Sleep quality in caregivers was assessed using the Chinese version of the Pittsburgh Sleep Quality Index (PSQI). Logistic regression was used to evaluate the association between aspects of the PSQI and injury. A propensity score model was used to generate a quasirandomized design. Results . This case-control study recruiting 277 injured and 274 noninjured children was conducted in Taiwan. There was no statistically significant difference in child's age and primary caregiver's age between the injured and noninjured groups. The primary outcome, Pittsburgh sleep quality index, was not significantly different between the two groups. The average scores of sleep duration and habitual sleep efficiency in the control group were higher than those in the case group. However, there was no difference between the two groups after adjusting via a propensity score model, including the following potential confounders, child's age, child's sex, number of previous injury, caregiver mental status, caregiver's sex and caregiver's age, and the number of children living together. Conclusion. Our study was the first to examine the association between injury in children and the sleep quality of their primary caregivers. We observed that no PSQI component significantly affected the risk of injury among children.